Developing a Social Media Marketing Plan for Viet Huong Ceramics Construction Joint Stock Company - Le, Thi My Linh (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Digital Marketing; 2021-2025.